2021
DOI: 10.36660/abc.20210921
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização do Miocárdio Guiada pela Fisiologia: Está na Hora do Cirurgião Cardíaco Incorporar a Reserva de Fluxo Fracionada na Prática?

Abstract: According to most recent international guidelines on myocardial revascularization, fractional flow reserve (FFR)-guided percutaneous coronary intervention should be considered in patients with multivessel disease. That would include evaluation of all lesions between 40 to 90% diameter stenosis before implanting a stent. 1,2 The same guidelines suggest prioritizing completeness of revascularization when the decision is made for coronary artery bypass graft surgery (CABG), which means bypassing all lesions >50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…One theoretical benefit of coronary artery bypass graft over PCI relies on the idea that the graft bypasses long segments of proximal coronary plaques, and the patient would be protected from MI if any of those ruptures, whereas the stents protect only the stented segment. 14 In conclusion, Kalkan et al 8 demonstrated that patients with higher CHA 2 DS 2 VASc score have higher rSS, which means higher CAD severity. Based on recent evidence, those patients might consequently be at higher risk of plaque rupture and cardiovascular events, such as MI or death, and therefore would benefit from more aggressive plaque stabilizing therapies.…”
mentioning
confidence: 87%
“…One theoretical benefit of coronary artery bypass graft over PCI relies on the idea that the graft bypasses long segments of proximal coronary plaques, and the patient would be protected from MI if any of those ruptures, whereas the stents protect only the stented segment. 14 In conclusion, Kalkan et al 8 demonstrated that patients with higher CHA 2 DS 2 VASc score have higher rSS, which means higher CAD severity. Based on recent evidence, those patients might consequently be at higher risk of plaque rupture and cardiovascular events, such as MI or death, and therefore would benefit from more aggressive plaque stabilizing therapies.…”
mentioning
confidence: 87%